Cross-cultural Adaptation and Validation of the Hausa Version of the Oswestry Disability Index 2.1a for Patients With Low Back Pain. Issue 18 (15th September 2019) - Adamu, Aisha S.; Ibrahim, Aminu A.; Ahmad, Rufa'i Y.; Akindele, Mukadas O.; Kaka, Bashir; Mukhtar, Naziru B.
Abstract : Study Design: Validation of a translated, culturally adapted questionnaire. Objective: To translate the Oswestry Disability Index (ODI) version 2.1a into Hausa Language and to validate its use in a cohort of patients with low back pain (LBP). Summary of Background Data: The ODI is one of the most commonly used condition-specific questionnaires for assessing functional disability in patients with LBP, yet, no formal cross-culturally adapted and validated Hausa version exists. Methods: The Hausa version of the ODI 2.1a (ODI-H) was developed according to established guidelines. Validation was performed among 200 patients with LBP recruited from both rural and urban Nigeria. Reliability was assessed using internal consistency (Cronbach α), test–retest reliability by computing intraclass correlation coefficient, standard error of measurement, and minimal detectable change. Convergent validity was assessed by correlating the ODI-H with Visual Analogue Scale for pain, Fear-Avoidance Beliefs Questionnaire, and finger-floor distance test. Divergent validity was assessed by correlating the ODI-H with age, educational level, and occupational status. Exploratory factor analysis (EFA) and confirmatory factor analysis were also performed. Confirmatory factor analysis was performed with three models: 1) one-factor theory-driven model, 2) two-factor theory-driven model (dynamic and static factors), and 3) a model based on our EFA. Results: The ODI-H had high internal consistency (Cronbach α = 0.87) and excellent test–retest reliability (intraclass correlation coefficient  = 0.937) with standard error of measurement and minimal detectable change being 3.69 and 10.2 respectively. The construct validity (convergent and divergent validity) is supported as all (6:6, 100%) the a priori hypotheses were confirmed. The EFA yielded a two-factor model explaining 54.3% of the total variance but demonstrated poor fit. The one-factor and two-factor theory-driven model had acceptable fit but the one-factor theory-driven model was better. Conclusion: The ODI-H version 2.1a was transculturally equivalent, reliable, and valid tool for assessing functional disability among Hausa-speaking patients with LBP. The use of this tool can be recommended for future clinical and research purposes. Level of Evidence: 3 Abstract : Supplemental Digital Content is available in the textThis study described the translation of the ODI version 2.1a into Hausa language, cross-cultural adaptation, and validation of the questionnaire in a cohort of patients with LBP. The results of the study suggest that the Hausa ODI version 2.1a is reliable and valid and can be recommended for future use.